Reliable protection of sugar beet sows from weedage in the foothill zone of the Republic of Adygeya - N. I. Mamsirov; T. N. Bondareva (Новые технологии, 2017)
The results of long-term studies on the establishment of optimal dosage of herbicide application in the cultivation of sugar beet on the chernozems of the leached Adygea Republic are presented. It has been established that the highest yield (24.5 t / ha) of sugar beet is achieved with the use of the Frontier Optima herbicide with the norm of 1.2 l / ha, soil - before the emergence of the crop. At the same time, the level of profitability of products was 123.7%. Similar results were obtained when using the Caribou herbicide, with a yield of 23.7 t / ha, the level of profitability of the products reached 123.4%.